Prevalence of Common Mental Disorder (CMD) in nursing students arising from academic lifestyle (Research, Society and Development, 2020)
Common mental disorders, also known as minor psychiatric disorders, are mild mental disorders, but they can have a long-term impact. The process of adapting to higher education requires attention, during this phase many changes occur, not only in academic life but also in the health of university students. The objective of this study is to identify the occurrence of common mental disorder in students of the Nursing course at UNIFACOL. This is a cross-sectional, quantitative and descriptive study, carried out in a Higher Education institution (HEI) located in the interior of Pernambuco with students from the 1st to the 10th year of the Bachelor of Nursing course. The 1st nursing period was excluded due to not having a sufficient number of students to compose this period. The sample was calculated based on the following parameters: estimated number of students enrolled (N= 370); Z= 1.96 (95.0% confidence level); Proportion of occurrence of the phenomenon of interest = 50.0% (0.5) and sampling error of 5.0% (0.05). Thus, the sample estimate was 148 undergraduate nursing students. The results show the prevalence of CMD per period: 2nd period of nursing 61.50% (n= 16), 3rd period 25% (n= 1), 4th period 100% (n= 14), 5th period 60% (n= 3), 6th period 71.40% (n= 10), 7th period 75% (n= 3), 8th period 73.33% (n= 11), 9th period 62.40% (n= 5), 10th period 54.13% (n= 13), being the most prominent in the 2nd period due to the fact that students have not yet adapted to college, causing stress and mental disorders. It is concluded that mental health is a topic that must be discussed, promoting the promotion, prevention and recovery of health, taking into account the risk of common mental disorders becoming more severe if not treated, which can interfere in the academic training cycle. , personal and social life.